(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical characteristics of dissociative symptoms in patients with mixed disorders of conduct and emotions. Subjects and methods: A cross-sectional descriptive study was conducted on 88 patients diagnosed with mixed disorders of conduct and emotions (F92) according to ICD-10 criteria, who were treated as inpatients at the National Institute of Mental Health, Bach Mai Hospital from August 2025 to June 2026. Data were collected through direct clinical interviews combined with medical records and analyzed using SPSS 20.0 software. Results: The study group had a mean age of 15.2 ± 2.04 years, with females accounting for 58%. The majority were aged 14-16 years (52.3%) and lived in urban areas (71.6%). Clinically, emotional instability was the most common symptom (68.2%), followed by violation of rules (76.1%). Notably, 51.1% of patients presented with concurrent emotional and behavioral symptoms from the onset. Dissociative symptoms of the somatic and motor types were predominant (53.4%), with pain being the most common somatic dissociative symptom (58.3%) and dissociative run (tremor) being the most prominent motor symptom (56.4%). All patients received pharmacotherapy (100%), 65.9% combined with psychotherapy, and 34.1% combined with neuromodulation. Conclusion: Mixed disorders of conduct and emotions are predominantly seen in female adolescents of school age living in urban areas. Dissociative symptoms, particularly of the somatic and motor types, are prominent. Combined treatment with pharmacotherapy, psychotherapy, and neuromodulation is an appropriate approach. Early detection and comprehensive intervention are necessary for this patient group.